Ball convergence for combined three-step methods under generalized conditions in Banach space - ARGYROS , Ioannis K.; BEHL, Ramandeep; GONZÁLEZ, Daniel; MOTSA, Sandile S. (Studia Universitatis Babeș-Bolyai Mathematica, 2020)
We give a local convergence analysis for an eighth-order convergent method in order to approximate a locally unique solution of nonlinear equation for Banach space valued operators. In contrast to the earlier studies using hypotheses up to the seventh Fr´echet-derivative, we only use hypotheses on the first-order Fr´echet-derivative and Lipschitz constants. Therefore, we not only expand the applicability of these methods but also provide the computable radius of convergence of these methods. Finally, numerical examples show that our results apply to solve those nonlinear equations but earlier results cannot be used. Mathematics Subject Classification (2010): 65G99, 65H10, 47J25, 47J05, 65D10, 65D99.